THE EFFECT OF VIDEO TUTORIAL MEDIA ON STUDENTS’ PRACTICAL UNDERSTANDING OF TUNE-UP PROCEDURES FOR THE 2010 TOYOTA AVANZA ENGINE - Yanari Rizki Utomo; Dwi Jatmoko; Aci Primartadi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
As a vocational automotive teacher from SMK Muhammadiyah Larangan, the authors often find chapter trials of Grade XI students (TKR) they have had trouble memorizing the correct sequence of stages tuning?motors for eg 2010 Toyota Avanza EFI engine, especially in determining the function TPS, MAP and IACV. A single live example from the teacher is often not enough: students?might miss some crucial part of it while taking notes, or be too shy to ask questions when they don’t understand something. To address this problem, the researcher used a classroom action research with 12 minute video?instructional media using smartphone creations and Avanza engine 2010 in school. Sixty Grade XI TKR students were selected for this study, divided into an Experimental Group (video learning method) and a Control Group (traditional demonstration method). The results showed: Mean of Experimental group: 85.0, average of the control group : 67.3. A total of 83.3% of the experimental group received marks for the category of Excellent, while the control group received 0%. The result of the independent t-test showed that there is a significant difference between the means of the two groups, since t(58) = 8.21 The aforementioned findings prove the effect of the use of cheap instructional videos prepared by lecturers to address the issue of resource equality for better access to independent learning for the students, which lies squarely within the principle of autonomy of the students under the Merdeka Curriculum of Indonesia.